2018
DOI: 10.1002/cpt.1094
|View full text |Cite
|
Sign up to set email alerts
|

S‐Nitrosylation of Prostacyclin Synthase Instigates Nitrate Cross‐Tolerance In Vivo

Abstract: Development of nitrate tolerance is a major drawback to nitrate therapy. Prostacyclin (PGI2) is a powerful vasodilator produced from prostaglandin (PGH2) by prostacyclin synthase (PGIS) in endothelial cells. This study aimed to determine the role of PGIS S-nitrosylation in nitrate tolerance induced by nitroglycerin (GTN). In endothelial cells, GTN increased PGIS S-nitrosylation and disturbed PGH2 metabolism, which were normalized by mutants of PGIS cysteine 231/441 to alanine (C231/441A). Clearance of nitric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 40 publications
(72 reference statements)
1
27
0
Order By: Relevance
“…In general, VitB6, in the form of PLP, is the coenzyme of 5 enzymes in these metabolic pathways: cystathionine‐β‐synthase, cystathionine‐γ‐lyase, cytoplasmic and mitochondrial serine hydroxymethyltransferase and glycine decarboxylase in the mitochondria . In this way, VitB6 regulates the transsulfuration pathway, which contributes to homocysteine regulation and provides cysteine synthesis . However, in this study, we reported that AMPK‐DOK3 pathway mediates VitB6’s actions of anti‐inflammation.…”
Section: Discussionmentioning
confidence: 66%
“…In general, VitB6, in the form of PLP, is the coenzyme of 5 enzymes in these metabolic pathways: cystathionine‐β‐synthase, cystathionine‐γ‐lyase, cytoplasmic and mitochondrial serine hydroxymethyltransferase and glycine decarboxylase in the mitochondria . In this way, VitB6 regulates the transsulfuration pathway, which contributes to homocysteine regulation and provides cysteine synthesis . However, in this study, we reported that AMPK‐DOK3 pathway mediates VitB6’s actions of anti‐inflammation.…”
Section: Discussionmentioning
confidence: 66%
“…6 As a matter of fact, myocardial fibrosis is the end-points of cell differentiation, activation and proliferation of cardiac fibroblasts. 36,37 For example, microRNA (miR) comprises small, non-coding RNA that binds to a specific 3'-untranslated region of mRNA and inhibits mRNA translation or promotes mRNA degradation. As concerned to why Prrx2 F I G U R E 5 Cell differentiation induced by TGF-β is abolished by gene silence of Prrx2 in cardiac fibroblasts.…”
Section: F I G U R E 4 Tgf-β Induces Cell Differentiation and Up-regumentioning
confidence: 99%
“…The gene function may be regulated in transcriptional, post-transcriptional and post-translational levels. 36,37 For example, microRNA (miR) comprises small, non-coding RNA that binds to a specific 3'-untranslated region of mRNA and inhibits mRNA translation or promotes mRNA degradation. 38,39 It has been reported that Prrx2 mRNA is a target of miR-212-5p in breast cancer.…”
Section: F I G U R E 4 Tgf-β Induces Cell Differentiation and Up-regumentioning
confidence: 99%
“…Isolated 14-3-3 proteins, as potential protein partners of PTGIS, can recognize the canonical phosphorylated motifs of PTGIS protein in predicted amino acid positions 24–36, 75–82, 200–206, 223–232 using the online server [36] (). Other ways of post-translational regulation of prostacyclin synthase activity have been described to occur via reversible or irreversible S-nitrosylation [35,37], as well as S-glutathionylation of Cys residues of PTGIS protein [38]. Thus, it can be speculated that isolation from testis tissue lysate of multifunctional protein glutaredoxin (GLRX) [39,40,41,42], as a potential protein partner of PTGIS, indicates a probable role of GLRX in the S-glutathionylation of PTGIS.…”
Section: Resultsmentioning
confidence: 99%